Service Quality Dimensions and Customer Satisfaction in Nepalese Banking Sector - Lamichhane, Basu Dev; Lama, Padam Bahadur; Lamichhane, Saujan; Pandey, Prerna; Lama, Surati (NPRC Journal of Multidisciplinary Research, 2025)
This study investigates the relationship between service quality dimensions-tangibility, reliability, responsiveness, assurance, empathy, and customer satisfaction variables. Service quality is an important factor of success in the banking industry since it directly influences client satisfaction and provides a competitive advantage. This study employed the descriptive and casual relational research approach. The primary information utilized in the study consisted of a total of 100 questionnaires that were found useful out of 190 disseminated questionnaires. Data analysis was carried out utilizing descriptive statistics, correlation, and regression analysis. The findings showed that all service quality dimensions have a considerable beneficial impact on customer satisfaction, with a focus on tangible service components such as reliability, responsiveness, competence assurance, and sympathetic interactions. The findings imply that improving these aspects can lead to better customer experiences and satisfaction. From a policy standpoint, the study demonstrates the necessity for banks to improve their service quality in response to client expectations constantly. Financial organizations and other business entities can adopt these findings while deciding business and marketing policies.